LGBT victims of violence: An overview of European knowledge, policies and practices - Kovčo-Vukadin Irma (Temida)
Violent victimization of LGBT people is mostly focused on hate crime although the scope of their possible (and real) victimization is much broader. Since the scientific literature on this topic is dominantly from North America, the aim of this paper is an overview of European knowledge, policies and practices. Three questions are posed in the paper: 1) what are the European insights into the incidence of violent victimization of LGBT people, 2) how does European scientific interest into this topic look like, and 3) do European policies and practices serve as an adequate response to the violent victimization of LGBT people. The incidence of violent victimization of LGBT people ranges from 10% to 32%, with threats of physical violence being the main form. Victims report their victimization within the range of 17% to 22% of cases. The interest of European scientists in this problem is scarce and partial. Violent victimization of LGBT people is dominantly conceptualized in European policies and strategies through the constructs of discrimination and hate crime.